Does Money Explain Asset Returns? Theory and Empirical Analysis. - Chan, K C; Foresi, Silverio; Lang, Larry H P (Journal of Finance, 1996)
A cash-in-advance model of a monetary economy is used to derive a money-based capital asset pricing model (M-CAPM), which allows the authors to implement tests of asset pricing restrictions without consumption data. A test as in Eugene F. Fama and James D. Macbeth (1973) of the model suggests that the money betas have some explanatory power for the cross-sectional variation of expected returns; however, the model is rejected using conditional information. Consistent with their predictions, estimates of the curvature parameter are lower than those of the consumption capital asset pricing model (C-CAPM) and pricing errors of the M-CAPM tend to be smaller than those of the C-CAPM.